Assessing a recent South Korean cohort study of cancer risk following diagnostic radiation exposure at younger ages - McBain-Miller, Jasmine; Scurrah, Katrina J.; Mathews, John D. (Quantitative Imaging in Medicine and Surgery; Vol 10, No 2 (February 21, 2020): Quantitative Imaging in Medicine and Surgery, 2020)
We welcome the recent South Korean cohort study by Hong et al. (1), which estimated cancer risks following low-dose diagnostic radiation exposure before age 20. This study captured 12,068,821 patients from a nationally representative sample of South Korean residents. The study is larger than previous paediatric CT cohort studies (2-7), exceeding the number of CT exposed individuals (n=1,179,021) of all previous studies combined; though this advantage is offset by relatively short follow-up time. Including all forms of diagnostic radiation (not just CT scans), this study had a total of 1,275,829 individuals exposed to at least one low-dose medical radiation procedure. This important study of paediatric imaging is the first from South Korea, and the second from Asia, following the work of Huang et al. (4). Our commentary compares and contrasts this new study with earlier studies, highlighting advantages, potential limitations and outstanding questions.